Has the Restructuring of Chinese Central Stated-Owned Enterprises Achieved the Goal of International Expansion? - Wang, Xia; Gao, Cencen; Feng, Mingming (Journal of Applied Business and Economics, 2022)
Using the difference-in-differences method, we examine the internationalization effects of the restructuring of Chinese Central State-owned Enterprises (CCSOEs) during the years 2003 and 2016. We find that restructured CCSOEs have not achieved a higher degree of internationalization. Indeed, the higher the degree of internationalization after the CCSOE restructuring, the worse the firm’s performance. Overall, the results suggest that the Chinese government’s attempt to promote CCSOE internationalization through restructuring has not achieved its goal. Rather than governmental support and intervention, accelerating market-oriented reforms, weakening or eliminating administrative monopolies in the domestic market, and reducing the monopoly profits of CCSOEs in the domestic market could be more effective approaches to promote CCSOE internationalization.